Thalamo-Cortical White Matter Underlies Motor Memory Consolidation via Modulation of Sleep Spindles in Young and Older Adults. (15th March 2019) - Vien, Catherine; Boré, Arnaud; Boutin, Arnaud; Pinsard, Basile; Carrier, Julie; Doyon, Julien; Fogel, Stuart
Highlights: Post-learning changes in spindles relate to thalamo-cortical tracts microstructure. Spindles mediate the relationship between FA and motor memory consolidation. This structure–behavior relationship appears to be preserved along the agespan. Abstract: Ample evidence suggests that consolidation of the memory trace associated with a newly acquired motor sequence is supported by thalamo-cortical spindle activity during subsequent sleep, as well as functional changes in a distributed cortico-striatal network. To date, however, no studies have investigated whether the structural white matter connections between these regions affect motor sequence memory consolidation in relation with sleep spindles. Here, we used diffusion weighted imaging (DWI) tractography to reconstruct the major fascicles of the cortico-striato-pallido-thalamo-cortical loop in both young and older participants who were trained on an explicit finger sequence learning task before and after a daytime nap. Thereby, this allowed us to examine whether post-learning sleep spindles measured using polysomnographic recordings interact with consolidation processes and this specific neural network. Our findings provide evidence corroborating the critical role of NREM2 thalamo-cortical sleep spindles in motor sequence memory consolidation, and show that the post-learning changes in these neurophysiological events relate specifically to white matter characteristics in thalamo-cortical fascicles. Moreover, we demonstrate that microstructure along this fascicle relates indirectly to offline gains in performance through an increase of spindle density over motor-related cortical areas. These results suggest that the integrity of thalamo-cortical projections, via their impact on sleep spindle generation, may represent one of the critical mechanisms modulating the expression of sleep-dependent offline gains following motor sequence learning in healthy adults.